Effect of mercury on the growth and biochemical behavior of nostoc muscorum and anabaena variabilis (Funded work) - YOGESH NEGI,; SUNIL SHARMA,; BARIHUN THYRNIANG,; FRANKIE J. LALOO,; SAMRAT ADHIKARI, (International Journal of Pharma and Bio Sciences, 2019)
Cyanobacteria are a highly diversified group of photosynthetic organisms which can be exploited as a potential candidate for bioremediation processes. The present study evaluates the toxic effect of a heavy metal, mercury (Hg2+ (II)), on the growth and biochemical aspects of Nostoc muscorum and Anabaena variabilis. The results depicted negative effects of Hg2+ on cyanobacteria by hampering normal growth and physiological activities. The treated cells showed diminishing growth pattern and decrease in the photosynthetic pigments. Significant decline was also revealed in the biomass and lipid content. The LC50 value of Hg was determined to be 0.6µM for both the cultures. Activity of the enzymes involve in nitrogen metabolism such as Glutamine Synthetase (GS), Nitrate Reductase (NR) and Nitrite Reductase (NIR) were studied and showed reduced activity. This decreased activity also correlates with the reduction in the heterocyst frequency as obtained in the results. In contrast, the enzyme superoxide dismutase (SOD) and proline content concerned with stress management in cyanobacterial cells showed significant increase in activity. The result obtained in the present study exemplifies the cytotoxic environment created by the Hg2+ ions on the microbial cultures by altering their membrane’s physiological functions. Thus, causing leaching of photosynthetic pigments leading to decreased photosynthetic efficiency and consequently restraining growth. The growth inhibiting effect of Hg2+ ions was also evident from the reduced activity of enzymes entailed with assimilation and uptake of nitrogen, resulting in decline in heterocyst frequency. Furthermore, the apparent increase in cell’s SOD and proline content can be ascribed to the production of reactive oxygen species (ROS) due to heavy metal stress created by the Hg2+ ions.